2021
DOI: 10.1101/2021.01.31.21250702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CSF Aβ38 levels are associated with Alzheimer-related decline: implications for γ-secretase modulators

Abstract: Objective: Shorter Aβ species might modulate disease progression in Alzheimer's disease (AD). Here we studied whether Aβ38 levels in cerebrospinal fluid (CSF) are associated with risk of developing AD dementia and cognitive decline. Methods: CSF Aβ38 levels were measured in 656 individuals across two clinical cohorts - the Swedish BioFINDER study and the Alzheimer's Disease Neuroimaging Initiative (ADNI). Cox regression models were used to evaluate the association between baseline Aβ38 levels and risk of AD de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nevertheless, a metaanalysis pointed no signi cant difference in Aβ 1-38 levels between AD individuals and control group after comparing eight studies (34). Cullen and colleagues more recently demonstrated that higher CSF Aβ 1-38 levels are negatively associated with cognitive decline and risk of developing AD (35). In this context, it is evident that the potential of this isoform to add information in the preclinical stage of the disease remains under-explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a metaanalysis pointed no signi cant difference in Aβ 1-38 levels between AD individuals and control group after comparing eight studies (34). Cullen and colleagues more recently demonstrated that higher CSF Aβ 1-38 levels are negatively associated with cognitive decline and risk of developing AD (35). In this context, it is evident that the potential of this isoform to add information in the preclinical stage of the disease remains under-explored.…”
Section: Discussionmentioning
confidence: 99%